Elite level development rates and age-based performance patterns for the men`s throwing events - Babbit, D.; Saatara, M. (Track Coach, 2020)
A statistical analysis was performed on data taken from 23 or 24 of the top performers of all-timein the men`s throwing events. The purpose was to generate an age-based table of performancenorms for the all-time best throwers in each throwing event, and compare and contrast thedevelopmental rates of the four throwing disciplines as they pertain to reaching top performance.Age-based norms were created by calculating the average best mark of the top athletes for eachyear between18 to 30 years of age. The rate of development as it pertains to biological age wascalculated for each throwing discipline by creating a chart which plots the percentage of a givengroup`s maximum performance for that year relative to their best all-time performance. Resultssuggest that the javelin was the fastest developing event to best performance, while the hammerand discus throws displayed the slowest rates of development.This statistical study was influenced by the work of Pavel Tilinger, Karel Kovar, and Petra Hlavata intheir study on the dynamic progress of performances of prominent world-class athletes inselected track and field events from 20051. While the Tilinger, et al study examined data from avariety of running and field events, the scope of this project was focused exclusively on the men`sthrowing events with the subject groups consisting of 23 or 24 of the all-time performers in eachof the four throwing disciplines (shot put, discus, javelin, and hammer). The members of theseelite subject groups have shown to be the predominant medal winners at the sport`s highestlevels (Olympic Games and World Championships). The purpose of the study was to inspect theperformance data in a way to give an idea of what to expect when striving for elite performance: 1. Calculate the average age of top performance for each of the four throwing disciplines. 2. Generate an age-based table of performance norms for the all-time best throwers in eachthrowing event. 3. Compare and contrast the developmental rates of the four throwing disciplines as they pertainto reaching top performance.